2020
DOI: 10.3389/fenvs.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Safely Managed Sanitation in Urban Areas; Lessons Learned From a Global Implementation of Excreta-Flow Diagrams

Abstract: The urban population will rise to 6.7 billion by 2050. The United Nations has committed to provide everyone with safely managed sanitation, but there is limited understanding of the scale of the challenge. This paper describes a methodology for rapid assessment of sanitation in cities including a graphical representation (a shit-flow diagram or SFD) and reports on findings from implementation in 39 cities. The SFD provides high level information for planning purposes covering the entire sanitation system in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…Recent WHO (2018) design guidelines require that wet pit latrines only be used in areas of deep groundwater, and that if groundwater is used for domestic water supply then: pits should be located at least 1.5 m above the water table; 15 m horizontally down-gradient from the water supply; no graywater should be added; and septic tanks should discharge to a soak pit or leach field. However, appropriately designed soak-aways and absorption trenches are typically missing in dense urban areas or may be used in unfavorable groundwater conditions (high water table, highly porous soils) (World Bank, 2015;Peal et al, 2020). In addition, research has found that the travel distance of pathogens varies widely, questioning the validity of generalized separation guidance between pits and wells (Williams and Overbo, 2015).…”
Section: Contaminationmentioning
confidence: 99%
“…Recent WHO (2018) design guidelines require that wet pit latrines only be used in areas of deep groundwater, and that if groundwater is used for domestic water supply then: pits should be located at least 1.5 m above the water table; 15 m horizontally down-gradient from the water supply; no graywater should be added; and septic tanks should discharge to a soak pit or leach field. However, appropriately designed soak-aways and absorption trenches are typically missing in dense urban areas or may be used in unfavorable groundwater conditions (high water table, highly porous soils) (World Bank, 2015;Peal et al, 2020). In addition, research has found that the travel distance of pathogens varies widely, questioning the validity of generalized separation guidance between pits and wells (Williams and Overbo, 2015).…”
Section: Contaminationmentioning
confidence: 99%
“…According to the Joint Monitoring Programme (JMP), a safely managed sanitation service means that people should use improved sanitation facilities that are not shared with other households, and the excreta produced should be treated and disposed in situ, stored temporarily, and then emptied and transported to treatment off-site or transported through a sewer with wastewater and then treated off-site. The ambition for a higher level of service-through technical improvement of existing sanitation systems or in the design and the implementation of new ones to reduce these public health risks is supported by the conclusions of recent WASH trials [2] and the development of tools such as the Shit/Excreta Flow Diagram [3] and the Pathogen Hazard Diagram [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, septic tanks, leach pit latrines, and lined pit latrines are widely used by households [4,17,18]. The term 'septic tank' is widely used in Indonesia to refer to all on-site systems including those that are not technically septic tanks [3,17]. In a watertight septic tank, the liquid effluent can only leave through the effluent pipe; there is no leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Container Based Sanitation (CBS) is a system where sealed toilet containers are regularly collected from households and transported to treatment facilities. CBS, if properly managed, ensures full containment of faecal waste, by contrast with onsite-infiltration systems (latrines, septic tanks) which usually discharge contaminated liquid effluent locally (Peal et al, 2020). Several CBS business models have emerged globally since 2010 providing a viable, low-cost sanitation option.…”
Section: Introductionmentioning
confidence: 99%